Predictors of Substance Use Latent Classes Among American Indian Youth Attending Schools On or Near Reservations - Swaim, Randall C. (Am J Addict, 2019)
BACKGROUND AND OBJECTIVES: Identical latent classes of substance use for 7 to 8 grade and 9 to 12 grade American Indian (AI) youth living on or near reservations suggest that patterns of substance use are established early among these youth. This study examines relationships of substance-related factors to latent class membership and whether these relationships differ by grade group. METHODS: In-school surveys were administered to 1503 7 to 8 grade and 1995 9 to 12 grade students from 46 schools on or near reservations during the 2009/2010 to 2012/2013 school years. Four-class latent class models of substance use were specified and five classes of substance-related factors (peers, substance availability, perceived harm, family, early initiation), plus grade level and gender, were evaluated as predictors. RESULTS: For 7 to 8 grade students, substance-related factors differentiated nonusers from users, while for 9 to 12 graders, these factors also differentiated types of users. Early initiation and peer factors were strongly related to class membership, while other factors were less strongly related. DISCUSSION AND CONCLUSIONS: Early initiation of alcohol or marijuana is strongly related to being in a substance-using class for AI youth. Because these youth tend to initiate use earlier that other US youth, prevention resources should be targeted to reaching them and their families before age 12. SCIENTIFIC SIGNIFICANCE: Predictors of latent classes of substance use were identified for reservation-based AI youth. While the classes were identical for 7 to 8 grade and 9 to 12 grade youth, predictors varied across grade group, which may inform how best to develop prevention efforts unique to middle and high school AI youth.